1997
DOI: 10.1172/jci119657
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to hypertension-induced renal damage in the rat. Evidence based on kidney-specific genome transfer.

Abstract: To test the hypothesis that genetic factors can determine susceptibility to hypertension-induced renal damage, we derived an experimental animal model in which two genetically different yet histocompatible kidneys are chronically and simultaneously exposed to the same blood pressure profile and metabolic environment within the same host. Kidneys from normotensive Brown Norway rats were transplanted into unilaterally nephrectomized spontaneously hypertensive rats (SHR-RT1.N strain) that harbor the major histoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 30 publications
2
71
0
Order By: Relevance
“…169 St Lezin et al 170 assumed that underlying genetic susceptibility factors, that is, the Rf loci on RNO1, which were originally identified in the FHH rat, 77,89,90 may contribute to renal failure in BN. 170 Subsequently, the authors introgressed a 22-cM segment of RNO1, which may overlap with Rf-2, Bpfh-1 and possibly with Rf-1 in FHH, 77,89,90 from normotensive BN/Cr rats into the hypertensive SHR/Ola background of the congenic strain SHR.BN-D1Mit3/Igf2 (Tables 2 and 3).…”
Section: Congenic Studiesmentioning
confidence: 99%
“…169 St Lezin et al 170 assumed that underlying genetic susceptibility factors, that is, the Rf loci on RNO1, which were originally identified in the FHH rat, 77,89,90 may contribute to renal failure in BN. 170 Subsequently, the authors introgressed a 22-cM segment of RNO1, which may overlap with Rf-2, Bpfh-1 and possibly with Rf-1 in FHH, 77,89,90 from normotensive BN/Cr rats into the hypertensive SHR/Ola background of the congenic strain SHR.BN-D1Mit3/Igf2 (Tables 2 and 3).…”
Section: Congenic Studiesmentioning
confidence: 99%
“…This animal exhibits impaired renal autoregulation and severely diminished afferent arteriolar myogenic reactivity, although TGF is reported to be intact (160 -162). The Brown Norway rat (BNR) also exhibits impaired myogenic responses, but does not develop hypertensive renal injury because it normally exhibits a relatively low BP (33,164). However, as elegantly shown by Churchill et al (33), when exposed to hypertension by transplantation into the SHR, the BNR kidneys develop substantially more severe injury compared with the SHR kidneys.…”
Section: Consequences Of Impaired Renal Autoregulation On Renal Protementioning
confidence: 99%
“…In the rat remnant kidney model, hypertension develops following conventional 5/6 renal ablation by infarction, but not when renal mass is reduced by surgical excision (16,58,61). In the BNR, BP is not only typically reduced, but manipulations, such as DOCA/ salt, have minimal effects (33). Similarly, there is no evidence to date of detectable disturbances in volume homeostasis in the murine gene-deletion models lacking TGF (e.g., Ref.…”
Section: Consequences Of Impaired Renal Autoregulation On Volume Homementioning
confidence: 99%
“…Early studies from animal models with Dahl salt-sensitive rats, Spontaneous Hypertensive Rats, Fawn-hooded rats and Brown and Norway rats as well as the results of the AASKD trial suggested a genetic susceptibility to hypertensive vascular damage (Brown et al, 1996;Churchill et al, 1997;Freedman et al, 1998;Zarif et al, 2000;Agodoa et al, 2001). Several genetic alterations have been associated to a more rapid decline of renal function in AfricanAmerican patients with hypertensive nephrosclerosis.…”
Section: Epidemiology Of Hypertensive Nephrosclerosismentioning
confidence: 99%